2022
DOI: 10.3390/en15176456
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Carbon Neutrality Pledge through Clean Energy Transition: Linking the Role of Green Innovation and Environmental Policy in E7 Countries

Abstract: Most countries, notably those that signed the Paris Climate Agreement, prioritize achieving the zero carbon or carbon neutrality aim. Unlike earlier studies, this one assesses the contribution of environmental policy, clean energy, green innovation, and renewable energy to the E7 economies’ achievement of carbon neutrality goals from 1990 to 2019. Findings emanating from the study show that the EKC hypothesis is valid in E7 countries. Implying that emissions in the E7 countries increased with the kick-off of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 110 publications
1
14
0
Order By: Relevance
“…Study of Jiang et al (2022) found conjecture the crowding-out effects of environmental investments on enterprise innovation-related expenditures. Another study finds that REC, environmental tax, and TI minimized the environmental degradation (Yu et al, 2022).…”
Section: Problem Statementmentioning
confidence: 99%
“…Study of Jiang et al (2022) found conjecture the crowding-out effects of environmental investments on enterprise innovation-related expenditures. Another study finds that REC, environmental tax, and TI minimized the environmental degradation (Yu et al, 2022).…”
Section: Problem Statementmentioning
confidence: 99%
“…conducted a full theoretical analysis and empirical recommendations on carbon emission reduction in China's construction industry, and further improved the existing research on carbon emission reduction of relevant industries from the perspective of input-output analysis. Among the remaining studies on other countries in the world for low carbon, carbon neutral, Yu et al (2022) evaluated the contribution of several factors such as environmental policies and clean energy to achieve carbon neutral goals in G7 economies, and concluded that countries should abandon the use of fossil fuels to adopt clean energy sources such as electricity, thus making a radical energy change. With China's proposed carbon neutral development goal, carbon reduction actions in developed countries have become a hot issue in climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in energy and environmental economics have assessed the link between energy utilisation and environmental quality in both panel and time series frameworks (see Adebayo, 2021; Adebayo, Oladipupo, et al, 2021; Asongu et al, 2020; Awodumi & Adewuyi, 2020; Bano et al, 2021; Hossain et al, 2022; Jahanger, Hossain, Onwe, et al, 2023; Jahanger, Hossain, Usman, et al, 2023; Jahanger, Ozturk, et al, 2023; Majeed et al, 2021; Malayaranjan & Sahoo, 2020; Qashou et al, 2022; Rafindadi, 2015, 2016a; Rafindadi & Ozturk, 2015, 2017; Rafindadi & Usman, 2021; Soylu et al, 2021; Thai‐Ha et al, 2020; Yu et al, 2022). Nevertheless, the studies that investigated the effect of renewable (REN) and nonrenewable energy (NRE) use and real estate investment on environmental quality (ENQ) need to be more detailed and restricted to panel data framework (Fan & Zhou, 2019).…”
Section: Introductionmentioning
confidence: 99%